The Role of the Department of Education and Culture of Pesisir Selatan Regency in Supervising the Employee Performance Target (SKP) Filling in the E-Kinerja Application - Sabrina, Azwa; Magriasti, Lince (The Future of Education Journal, 2026)
Filling the Employee Performance Target (SKP) through the e-Kinerja application is an essential instrument in realizing accountability and improving the performance of civil servants, including in the education sector. This study focuses on the role of the Department of Education and Culture of Pesisir Selatan Regency in supervising the filling of the SKP for school principals through the e-Kinerja application, identifying the obstacles encountered, and examining the efforts made to improve supervision effectiveness. The research approach used is qualitative with a descriptive method. The data were obtained through interviews and document studies. The results show that the Department of Education and Culture has carried out supervisory roles through socialization, technical assistance, coordination with supervisors, and administrative monitoring of SKP filling. However, the effectiveness of supervision is not yet optimal due to limited human resources, low conceptual understanding of school principals regarding performance-based SKP, limited information technology competence, and the suboptimal technical guidelines for filling SKP. Therefore, there is a need for strengthening continuous performance development and evaluation to make the SKP filling through e-Kinerja more effective as a tool for assessment and improving the performance of school principals.